Community Empowerment Through Organic Waste Management Training Based on Biopori for Health Cadres at Puskesmas Depok II, Sleman - Alvin Hidayat; Nadia Naqa Nuri; Nisa Nur Aziza; Sardjito Eko Windiarso; Heru Subaris Kasjono (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2026)
nadequate household waste management, particularly the absence of proper segregation between organic and inorganic waste, continues to pose environmental health challenges in many Indonesian communities. To address this issue, a community service program was implemented involving 39 health cadres from Puskesmas Depok II, Sleman, Yogyakarta. The program aimed to strengthen participants’ knowledge and practical competencies in managing organic waste through the application of biopore technology. Activities were designed based on the Awareness, Interest, Evaluation, Trial, and Adoption (AIETA) framework and consisted of Environmental Health Inspections (IKL), educational counseling, Community Self Survey (CSS) activities, and practical biopore-making trainingsessions. The effectiveness of the intervention was evaluated using a pre-test and post-test approach. Results of the Shapiro–Wilk test indicated that both datasets were not normally distributed (p = 0.001). Consequently, differences in participants’ knowledge scores were analyzed using the Wilcoxon Signed Rank Test. Statistical analysis demonstrated a significant increase in knowledge following the intervention, as indicated by a Z value of −5.554 and an Asymp. Sig. (2-tailed) value of 0.000. Furthermore, all participants showed higher post-test scores, with positive ranks observed in all 39 respondents and no negative ranks or ties recorded. These findings suggest that the program was effective in improving both knowledge and practical skills related to organic waste management. Continued implementation of biopore education and regular monitoring by Puskesmas are recommended to maintain long-term behavioral change.